2018
DOI: 10.1016/j.cmet.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Adipose Tissue Imaging Reveals Regional Variation in Beige Fat Biogenesis and PRDM16-Dependent Sympathetic Neurite Density

Abstract: While the cell-intrinsic pathways governing beige adipocyte development and phenotype have been increasingly delineated, comparatively little is known about how beige adipocytes interact with other cell types in fat. Here, we introduce a whole-tissue clearing method for adipose that permits immunolabeling and three-dimensional profiling of structures including thermogenic adipocytes and sympathetic innervation. We found that tissue architecture and sympathetic innervation differ significantly between subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
223
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 238 publications
(240 citation statements)
references
References 24 publications
15
223
2
Order By: Relevance
“…Using volume fluorescence-imaging techniques to visualize the neural arborizations in mouse inguinal WAT, it was recently shown that sympathetic fibres are in close apposition to over 90% of adipocytes 34 . Supporting these observations, investigators recently developed an Adipo-Clear model in which fat pads were delipidated to enable 3D whole-tissue imaging and found dense staining of sympathetic fibres in close contact with the majority of adipocytes in inguinal WAT 99 . Interestingly, blocking the outgrowth of neural fibres to inguinal WAT using genetic or pharmacologic tools prevented the sympathetic arborization of the tissue and the ability of cold to promote the development of brite adipocytes 34 .…”
Section: Leptin and Adipose Functionsmentioning
confidence: 93%
See 1 more Smart Citation
“…Using volume fluorescence-imaging techniques to visualize the neural arborizations in mouse inguinal WAT, it was recently shown that sympathetic fibres are in close apposition to over 90% of adipocytes 34 . Supporting these observations, investigators recently developed an Adipo-Clear model in which fat pads were delipidated to enable 3D whole-tissue imaging and found dense staining of sympathetic fibres in close contact with the majority of adipocytes in inguinal WAT 99 . Interestingly, blocking the outgrowth of neural fibres to inguinal WAT using genetic or pharmacologic tools prevented the sympathetic arborization of the tissue and the ability of cold to promote the development of brite adipocytes 34 .…”
Section: Leptin and Adipose Functionsmentioning
confidence: 93%
“…4). Moreover, the pattern of SNS innervation of fat pads differs in mice, with minimal fibres projecting to gonadal WAT compared with inguinal WAT 99 . The regional specificity of SNS innervation is further emphasized by functional changes (reflected by differences in noradrenaline turnover) observed following treatment with various stimuli.…”
Section: Figurementioning
confidence: 99%
“…Toward this goal, we adapted the delipidation methods of the AdipoClear protocol (Chi, Wu et al 2018), which was developed to clear and immunolabel lipid dense adipose tissue without damaging tissue structure. A schematic of this modified protocol with relevant additions and substitutions is shown in Fig.1A, alongside rat brain hemisphere cleared with this new protocol (Fig1C), as compared to results of the previous version of the protocol (Fig1B).…”
Section: Results Idisco+ Delipidation and Clearing For Rat Brain Tissuementioning
confidence: 99%
“…First, we can detect fluorescence without any injection, and this characteristic allows us to easily detect fluorescence in neonatal mice, as shown in Fig. This method revealed that UCP1 expression strongly correlates with sympathetic innervation [62,63]. UCP1-mRFP1 BAC Tg mice are also suitable for evaluation of pharmacological UCP1 stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a tissue clearing method is used as a new method for histological analysis of adipose tissue. This method revealed that UCP1 expression strongly correlates with sympathetic innervation [62,63]. However, three-dimensional distribution of the UCP1 is still unknown.…”
Section: Discussionmentioning
confidence: 99%